An optimization of part distortion for a structural aircraft wing rib: an industrial workflow approach - Barcenas, Leonardo; Ledesma-Orozco, Elias; Van-der-Veen, Sjoerd; Reveles-Arredondo, Francisco; Rodríguez-Sánchez, E. Alejandro (CIRP journal of manufacturing science and technology, 2020)
Inherent residual stresses in the raw material of large monolithic structural components cause distortion when parts are machined. This is a frequent problem in the manufacturing life cycle of aircraft parts that has resulted in recurring concession, rework or scrap, which cost millions of euros to the aerospace industry. In this study an industrial workflow was implemented to predict and optimize part distortion after the machining of a representative structural aircraft-component. This was carried out by means of the following steps: i) characterization of inherent residual stresses of a material using a modified layer removal method; ii) generation of residual stress profiles using part-distortion measurements; and iii) optimization of distortion using Finite Element Analysis to derive an optimal part location. The workflow was validated with three experiments from two aluminum 7050-T7451 specimens with different residual stress states. A prediction of distortion with a Finite Element model resulted in 0.44mm from the higher residual stresses while from the lower residual stresses the maximum distortion was 0.36mm. The experimental testing was carried out in a CNC center to validate the numerical results. Good agreement from the numerical results in regards experimental tests led to propose the optimal part location which decreased the distortion up to 0.12mm.